The Influence of Perception of Exploitation and Perception of Job Obtaining on The Welfare Through Job Satisfaction as a Mediating Variable - Dwi Safitri, Ika; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2026)
This study aims to analyze the influence of perceived exploitation and perceived job security on the well-being of online motorcycle taxi drivers, with job satisfaction as a mediating variable. The development of the digital economy has given rise to new forms of platform-based employment relationships, such as those of online motorcycle taxi drivers. Algorithmic systems and partnership status create a paradox between flexibility and uncertainty that has the potential to impact worker well-being. This quantitative study employed a survey approach, targeting 240 active online motorcycle taxi drivers in the Greater Jakarta Indonesia area, who were selected through purposive sampling. The data was analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that perceived exploitation had a negative and significant effect on job satisfaction and well-being, while perceived job security had a positive and significant effect on job satisfaction and well-being. Job satisfaction also had a positive and significant effect on well-being and acted as a partial mediator in the relationship between perceived exploitation and perceived job security and well-being. These findings suggest that the well-being of online motorcycle taxi drivers is not only influenced by the pressures of platform-based work systems but is more strongly determined by the extent to which the work is perceived to provide benefits and fairness, as reflected in the level of job satisfaction.